Buddhist diplomacy: potential for regional cohesion - Chia, Jack Meng-Tat (2022)
In recent years, a number of Asian countries have increasingly turned to Buddhism as a balm to relieve tense relations and foster cultural understanding. Buddhist diplomacy has the potential to encourage regional cohesion and interfaith harmony in the region.